2008
DOI: 10.1111/j.1600-065x.2008.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and challenges for eliciting immunity against avian influenza virus in birds

Abstract: Vaccines and vaccination have emerged during the past two decades as essential tools in avian influenza (AI) control for poultry, because they increase resistance to infection, prevent illness and death, reduce virus replication and shed from respiratory and alimentary tracts, and reduce virus transmission to birds and mammals, including humans. Such protection in birds is primarily mediated by homosubtypic humoral immunity against the hemagglutinin protein, but cell-mediated and innate immunity contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
108
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 128 publications
(183 reference statements)
1
108
0
1
Order By: Relevance
“…), diagnostics and surveillance, elimination of infected poultry, and potentially decreased poultry susceptibility (i.e., after vaccination) (42). One of the goals of this study was to evaluate both Mexican and U.S. H7 LPAI viruses as potential vaccines for control of the H7N3 HPAI virus.…”
Section: Discussionmentioning
confidence: 99%
“…), diagnostics and surveillance, elimination of infected poultry, and potentially decreased poultry susceptibility (i.e., after vaccination) (42). One of the goals of this study was to evaluate both Mexican and U.S. H7 LPAI viruses as potential vaccines for control of the H7N3 HPAI virus.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, antibodies and viruses coexist. In turn, so-called "escape mutants" resulting from antigenic drift of the viruses are selected (40). These escape mutants are less susceptible to vaccine-induced neutralizing antibodies.…”
mentioning
confidence: 99%
“…13 Our previous study showed that chickens given an oral H5 DNA vaccine using AgNPs as a carrier showed antibody and T cell responses with enhanced Th1-like cytokine expression in the spleen. 11 However, there is no direct evidence of specific cytokines induced by hemagglutinin of avian influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…11 Spread of the highly pathogenic avian influenza virus (H5N1) remains a major global concern. 13 The development of safe and efficient avian influenza vaccines for animal and human use is essential for preventing panzootic influenza and pandemics worldwide. Protective immunity against avian influenza depends largely on development of the immune response against hemagglutinin glycoprotein.…”
Section: Introductionmentioning
confidence: 99%